Faktor Yang Mempengaruhi Terjadinya Kecelakaan Kerja Penderes Pohon Kelapa Di Kecamatan Bahorok - Dea Ananda Br.SK; Susilawati Susilawati (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Work accidents in coconut tree harvesting are a serious problem that affects occupational safety and health in Bahorok District, Indonesia. Using a qualitative approach with a case study design, the research was conducted through interviews and direct observation of five coconut tree growers in coconut plantations owned by local residents. The research results show that a lack of knowledge about work risks, inadequate attitudes towards work safety, and the habit of not using personal protective equipment (PPE) correctly are the main factors causing work accidents. Renderers often ignore the slippery and fragile condition of trees and existing safety procedures, prioritizing work speed over safety. Education regarding work risks, changing attitudes towards the importance of work safety, as well as enforcing rules and using appropriate PPE are very necessary. The implementation of these steps is expected to reduce the accident rate and create a safer and healthier work environment for coconut tree harvesters in Bahorok District.